Looking at the Overlooked: Four Essays on Still Life Painting - Bryson, Norman 1949- (London Reaktion Books, 2018)
Historically and culturally, the societies that produced still life painting could hardly be more diverse. What is it, then, that allows us to place such different types of image in a single category? Norman Bryson argues that the family resemblances between the different types of still life stem from their common portrayal of a level of material culture that retains its fundamental outlines through long spans of time and across the boundaries and divisions of national culture: the culture of domestic routine and the rituals of hospitality. How this 'low plane reality' is historically viewed and inflected by the 'higher' levels and discourses of the surrounding culture is the fundamental subject of this book.
Includes bibliographical references (pages 179-189).
Keywords: Fine art